2015
DOI: 10.1155/2015/590470
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tea Tree Oil (Melaleuca alternifolia) on Fluconazole Activity against Fluconazole-ResistantCandida albicansStrains

Abstract: The aim of this study was to evaluate the activity of fluconazole against 32 clinical strains of fluconazole-resistant Candida albicans, and C. albicans ATCC 10231 reference strain, after their exposure to sublethal concentrations of tea tree oil (TTO) or its main bioactive component terpinen-4-ol. For all tested fluconazole-resistant C. albicans strains TTO and terpinen-4-ol minimal inhibitory concentrations (MICs) were low, ranging from 0.06% to 0.5%. The 24-hour exposure of fluconazole-resistant C. albicans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 55 publications
2
49
0
12
Order By: Relevance
“…All Candida strains tested, including the reference strains and the azole‐resistant strain AIDS 68, were shown to have no growth in either TTO‐VS or TTO, with a fungal load reduction of around 1.5 log. The data are in substantial agreement with those obtained by the viability test that showed 100% of fungicidal activity starting from 24 h of TTO treatment (Mertas et al ., ; Mondello et al ., ). A fungicidal activity, though to a lower magnitude, was also shown against the azole‐resistant C. albicans AIDS68 strain, as shown by >80% drop of cfu/mL within 60 min at a TTO concentration of 0.5% v/v (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All Candida strains tested, including the reference strains and the azole‐resistant strain AIDS 68, were shown to have no growth in either TTO‐VS or TTO, with a fungal load reduction of around 1.5 log. The data are in substantial agreement with those obtained by the viability test that showed 100% of fungicidal activity starting from 24 h of TTO treatment (Mertas et al ., ; Mondello et al ., ). A fungicidal activity, though to a lower magnitude, was also shown against the azole‐resistant C. albicans AIDS68 strain, as shown by >80% drop of cfu/mL within 60 min at a TTO concentration of 0.5% v/v (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This study immersed the denture in tea tree oil for 24-48 hours instead of adding it in the denture itself. Our study has added tea tree oil into the soft liner so that there is continuous sustained release of Copaiba oil, Propolis (Red, Brazilian) and Propolis (Chilean, Rotterdam Laboratory) exhibiting antifungal activity up to 60 days, avoiding other alternative mechanical and chemical denture cleansing methods [29]. We are currently investigating the detailed mechanism and incorporation of antimicrobial agent incorporation into the soft liner structure and results will be published in due course.…”
Section: Discussion Of the Anti-microbial Properties Of The Soft Linementioning
confidence: 99%
“…An invitro study by Merta et al, [23] suggested that the clinical candida strains that are resistant to Fluconazole when exposed to sublethal concentrations of TTO and fluconazole, explored a change in the activity of Fluconazole. TTO enhanced the activity of Fluconazole against resistant strains and it was concluded that TTO can be used as a single therapy or in combination with other conventional drugs like Fluconazole that can be used to treat difficult yeast infections.…”
Section: Discussionmentioning
confidence: 99%